Learning in Immersive Virtual Worlds from the Perspective of Media Didactics - Salem, Asma Al Mokhtar Miftah Alhaj; Alfaqi, Rawad Mansour Abdulhafith; Alnagrat, Ahmed Jamah Ahmed (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Virtual Reality (VR) technologies are increasingly recognized for their potential to enrich educational settings, yet their integration often emphasizes technological novelty over pedagogical effectiveness. In the domain of media didactics, VR’s value lies not only in its immersive and interactive capabilities but also in its capacity to fulfill specific educational objectives through structured engagement. This study explores the role of immersive VR environments in supporting educational activities by aligning VR’s affordances—such as realism, interactivity, and user engagement—with established didactic principles. The primary objective is to provide a framework that encourages educators to implement VR in ways that are pedagogically sound, thereby enhancing learner engagement and skill acquisition. Using a qualitative approach, the study synthesizes recent literature and analyzes case studies within four key VR applications: training environments, construction tools, exploration experiences, and experimental simulations. Results indicate that VR significantly contributes to experiential learning across these domains, with applications including skill-based training in virtual workshops, exploratory learning through virtual field trips, and controlled experimentation that supports hypothesis testing in virtual worlds. The study concludes that VR holds transformative potential for education; however, its impact is maximized when embedded within a purposeful didactic framework. By aligning VR applications with clear educational goals, VR can foster cognitive and emotional engagement, improving learning outcomes across diverse disciplines.